Influence of the Constitutive Contact Law on the Anisotropic Material Parameters of Sheet-Layered Lamination Stacks - Baloglu, Maximilian Volkan; Willner, Kai (2018 8th International Electric Drives Production Conference (EDPC), 2018)
The specific design of components like rotor and stator as sheet-layered lamination stacks results in a structural behavior that is heavily dependent on the sheet interactions on the microscale. Due to the manufacturing process, these thin laminations may be just stacked and held together e.g. by welding or clamps, such that frictional contact of rough surfaces between single sheets is taking place and significantly affects the overall deformation behavior. Here, the elastic anisotropic, more precisely transversely isotropic, material parameters describing these lamination stacks are identified with the help of the homogenization taking efficiently care of the microstructure. For this purpose, different constitutive contact laws in normal direction capturing the sheet interactions by a penalty formulation and their effect on the macroscopic quantities are presented to emphasize the importance of this model parameter. Furthermore, it is shown that the derived stress-strain relation is identical to results of a numerical homogenization, where a representative volume element is simulated by the Finite-Element method incorporating Zero-Thickness elements for the contact simulation. The numerical results are finally compared to experiments showing a good accordance.<br
Keywords: lamination stack; homogenization; constitutive modeling; material modeling; contact mechanics